Phaidros - Plato, 428? BCE-348? BCE; Lehmuskoski, Niilo, 1888-1948 (Salt Lake City, UT : Project Gutenberg, 2019)
"Phaidros" by Plato is a dialogue written around 370 BC. Socrates and Phaedrus meet outside Athens to discuss a speech about love. Their conversation spirals into deeper questions about rhetoric, the human soul, and divine inspiration. Through three contrasting speeches and the famous chariot allegory, they explore whether it's better to favor a lover or non-lover, while examining what makes persuasive speech truly effective and how desire shapes human nature. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/Phaedrus_(dialogue)
Release date is 2019-05-04
E-text prepared by Tapio Riikonen
Keywords: Socrates, 470 BC-399 BC; Rhetoric -- Early works to 1800; Love -- Early works to 1800; Soul -- Early works to 1800